Identifikasi Boraks Dengan Indikator Alami Ekstrak Bunga Asoka (Ixora paludosa) - Harni Sepriyani; Mega Elfia; Elti Fitriani (LPPM Universitas Dharma Andalas, 2022)
Borax is one of the non-food additives that is prohibited from being used in food but is still often misused. Regulation of the Ministry of Health of the Republic of Indonesia in 2012 concerning food additives, prohibits the use of borax in food products because it can endanger health. Borax examination can be done quantitatively and qualitatively. In this study, qualitative identification of borax was carried out using a natural indicator, namely asoka flower extract (Ixora paludosa L.). Identification of borax was carried out on meatballs, noodles, tofu, crackers, rice cakes and nuggets. The results obtained are 4 samples of borax positive and 2 samples of negative borax. Samples that were positive for borax showed a color change from yellow to brownish red.